Pengaruh Kualitas Produk, Persepsi Harga, Promosi, Citra Merek, Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Melalui Keputusan Pembelian Sebagai Variabel Intervening Pada Restoran Cepat Saji MCD - Izzan Fikrie Noerfaidin; Nova Anggrainie (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
The purpose of this study is to determine and analyze the influence of product quality, price perception, promotion, brand image, service quality, and to determine which variables are most dominant in customer satisfaction through purchasing decisions as an intervening variable at MCD fast food restaurants. The analysis method used in this study is quantitative primary data, with the following tests conducted: convergent validity test, discriminant validity test, measurement method, reliability test, structural model, R-Square (R2) test, path coefficient test, specific indirect effect test, predictive relevance test, model fit test, and discrimination test. The data used in this study was collected through questionnaires, and valid data was successfully collected from 230 respondents. The sampling method used in this study was non-probability sampling with purposive sampling technique. The testing tool used was SmartPLS. The results showed that the variables of product quality, price perception, promotion, brand image, and service quality effect on customer satisfaction through purchasing decisions as an intervening variable at MCD fast food restaurants. The purpose of this study is to determine and analyze the influence of product quality, price perception, promotion, brand image, service quality, and to determine which variable is most dominant in customer satisfaction through purchasing decisions as an intervening variable at MCD fast food restaurants.